Primordial Odontogenic Tumor of Anterior Maxilla in a Young Male: A Case Report and an Updated Review of Literature. (January 2021) - Naina, Sivakumar; Narwal, Anjali; Devi, Anju; Kamboj, Mala; Pandiar, Deepak
Primordial odontogenic tumor (POT) is a recently designated benign mixed epithelial and mesenchymal odontogenic tumor and only sixteen cases have been reported worldwide till now. Here we report an another case of POT in a 14–year old boy who presented with an asymptomatic buccal enlargement in the right maxillary region for past 4–5 months. A well-defined, unilocular, radiolucent lesion with impacted teeth was observed radiographically. A detailed account of clinico-radiographical and histolological differential diagnoses along with an updated literature review has been presented.